Burnout Syndrome among Healthcare Workers in Lithuania as a Former Soviet Country - Deksnytė, Aušra; Aranauskas, Ramūnas; Kasiulevičius, Vytautas; Aranauskas , Lukas; Navickas, Alvydas; Jurkytė, Rugilė; Palinauskaitė, Karolina; Zlotnikovienė, Diana (Neurologijos seminarai, 2024)
Objective. Measure the prevalence of burnout syndrome (BOS) among the healthcare workers (HCW) in Lithuania and the factors influencing it. The respondents were asked to fill out an anonymous online questionnaire which included information on their gender, age, years of work experience, specialty, work hours per week, the average number of patients per day, salary, healthcare chain, and the healthcare sector they are working at. BOS was assessed by using the Copenhagen Burnout Inventory (CBI).Results. A total of 2 806 questionnaires were used in the final analysis. A high prevalence of BOS among the MS in Lithuania was noticed (74% of all respondents), which is more severe in comparison to foreign research. The most significant link with severe BOS was noticed among a high number of patients per day (22.69±14.96 versus 17.77±13.32, t=4.92), a large number of work hours per week (48.89±12.96 versus 46.34±10.77, t=2.54), and a younger age (59.27±14.06 versus 55.73±13.91, t=3.53). Doctors had the highest BOS score compared to nurses, residents, and other specialists (59.72±13.99 versus 57.33±14.13, t=2.4; 57.53±14.20, t=2.2; 54.06±15.22, t=5.67, respectively). No links between gender, years of work experience, salary, healthcare chain, healthcare sector, and BOS were observed.Conclusions. BOS is highly prevalent among Lithuania’s medical staff, and it is more prevalent than in most other EU and non-EU countries. A high number of patients per day, a large number of work hours per week, and a younger age were significantly linked with more severe BOS.